ANALISIS KUALITAS PELAYANAN APLIKASI SP4N-LAPOR DI DISKOMINFOSANDITIK KABUPATEN SUMEDANG - Kusdinar, Rika; Sudirman, Gustian; Hidayat, Kustawan; Sorafudin, Muhamad Fadhil; Nurhasanah, Nanan; Yusria, Sahla; Nursabila, Zahra (LPPM UNSAP & FISIP UNSAP, 2025)
The SP4N-LAPOR program was created to provide and provide public complaint service media to the public in making online complaints This study aims to find out how good is the quality of service provided when using the application the National Public Service Complaint Management System program through the People's Online Complaint Aspiration Service (SP4N-LAPOR) at the Sumedang Regency Communication and Informatics, Cryptography and Statistics Office has been implemented The method used in this research is a qualitative method with a type of descriptive analysis in which to determine the information using a purposive sampling technique with the informant, secretary, Head of Information and Public Communications, and 2 staff in the field of Information and Public Communications, namely First Expert - Computer Officer and Journalist. The techniques used in collecting data were literature study, field study and triangulation. The results of the study show that the National Public Service Complaint Management System The People's Online Complaint Aspiration Service (SP4N- LAPOR) at the Sumedang Regency Communication and Informatics, Encryption and Statistics Office is still not running well. There are still obstacles in it such as the lack of accuracy of program targets, lack of response from SKPD, and less optimal coordination between DISKOMINFOSANDITIK and SKPD. Based on the results of the research, there are several suggestions, including the need for Improvement of Socialization, for example collaborating with the sub-district SKPD to hold socialization, the need for SKPD performance assessment, improvement of human resources such as guidance and training.